Parenting Enhancement, Interpersonal Psychotherapy to Reduce Depression in Low-Income Mothers of Infants and Toddlers: A Randomized Trial - Beeber, Linda S. (Nurs Res, 2013)
BACKGROUND: Depressive symptoms and clinical depression are highly prevalent in low-income mothers and negatively affect their infants and toddlers. OBJECTIVES: To test interpersonal psychotherapy combined with parenting enhancement on depressive symptoms and parenting behavior, compared with usual care. METHOD: Mothers (n = 226) of Early Head Start infants and toddlers from the southeastern and northeastern United States were randomized to the intervention delivered in-home by psychiatric mental health advanced practice nurses or usual care delivered by generalist nurses. Rigorous clinical depressive symptom and depression assessments and videotaped, coded mother-child interactions were used as baseline and 14-, 22-, and 26-week postintervention measures. RESULTS: Both the intervention and control groups had significantly reduced Hamilton Rating Scale for Depression scores at each subsequent time point compared to baseline (p < .0001). However, only mothers receiving the intervention showed a significant increase in positive involvement with their child, as measured by closeness, positive affect, affection, and warm touch at T4 (t = 2.22, df = 156, p < .03). DISCUSSION: Both intervention and control conditions resulted in symptom reduction, but only the intervention mothers showed significant interaction changes with their child, an essential step in reducing the negative child outcomes associated with maternal depressive symptoms. Results suggest that a combination of generalist and specialist nurses could be used to treat depressive symptoms in these mothers. Further study with longer postintervention observation is needed to see if, over time, the intervention led to longer-lasting symptom reduction.